Dead to her : a novel - Pinborough, Sarah, 1972- (William Morrow, an imprint of HarperCollinsPublishers, 2020)
"For fans of Liane Moriarty, Liv Constantine and Lisa Jewell, a twisty psychological thriller about a savvy second wife who will do almost anything to come out on top from the New York Times bestselling author of Behind Her Eyes"--